Does citation matter? Research citation in policy documents as an indicator of research impact - an Australian obesity policy case-study - Robyn Newson; Lucie Rychetnik; Lesley King; Andrew Milat; Adrian Bauman (BMC, 2018)
Abstract Background Citation of research in policy documents has been suggested as an indicator of the potential longer-term impacts of research. We investigated the use of research citations in childhood obesity prevention policy documents from New South Wales (NSW), Australia, considering the feasibility and value of using research citation as a proxy measure of research impact. Methods We examined childhood obesity policy documents produced between 2000 and 2015, extracting childhood obesity-related references and coding these according to reference type, geographical origin and type of research. A content analysis of the policy documents examined where and how research was cited in the documents and the context of citation for individual research publications. Results Over a quarter (28%) of the policy documents (n = 86) were not publicly available, almost two-thirds (63%) contained references, half (47%) cited obesity-related research and over a third (41%) of those containing references used unorthodox referencing styles, making reference extraction laborious. No patterns, in terms of the types of documents more likely to cite research, were observed and the number of obesity research publications cited per document was highly variable. In total, 263 peer-reviewed and 94 non-peer-reviewed obesity research publications were cited. Research was most commonly cited to support a policy argument or choice of solution. However, it was not always possible to determine how or why individual publications were cited or whether the cited research itself had influenced the policy process. Content analysis identified circumstances where research was mentioned or considered, but not directly cited. Conclusions Citation of research in policy documents in this case did not always provide evidence that the cited research had influenced the policy process, only that it was accessible and relevant to the content of the policy document. Research citation across these public health policy documents varied greatly and is unlikely to be an accurate reflection of actual research use by the policy agencies involved. The links between citation and impact may be more easily drawn in specific policy areas or types of documents (e.g. clinical guidelines), where research appraisal feeds directly into policy recommendations.